معاییر تحدید القواعد الدستوریة دراسة تطبيقية على تشريعات المجلس الوطني لكوردستان العراق(1992-1996) - الدين, واحد عمر محي (Sulaimani Journal for Humanities, 2003)
In our research, we have dealt with the definition, the concepts of constitution and the criticisms directed to them. Thus, we have made a definition of constitution law from the perspective of objective criterion. We have also treated the types of constitution, patterns of making it, procedures of modifying it, terminating or abrogating it. After analysis and evaluation, we have given our view of each of the topics as well as highlighting the principles we have relayed upon. Moreover we have exposed and given interpretations to the laws of the Iraqi kurdistan national assembly during (1992-1996) in the light of the seven criteria employed to delimit and distinguish the constitutional rules from the normal rule (linguistic “logical”, historical, formal, objective, academic, modern) we came to the conclusion that the objective criterion is the most comprehensive least subject to criticism and consistent with the nature and essence of the specified laws in this research because in that period there wasn't constitutional law in the region in the formal concept “ constitution document " Nevertheless, based on the objective criterion these laws contain some principles of constitutional law in terms of nature, essence or characteristics. Finally, the research closes with a number of conclusions, recommendations and suggestions.